(untitled) (Docentes 2.0 Journal, 2023)
Knowledge management has acquired great notoriety and importance in creating a culture where knowledge is valued, shared, and managed in such a way that it constitutes a key factor in the development of societies. For this reason, knowledge management constitutes a fundamental aspect in the training of future teachers of the physical education specialty. This essay aims to show how knowledge management constitutes a fundamental aspect of training future teachers in the specialty of physical education. This essay was framed within the humanistic paradigm since it seeks to establish a high valuation in all the individuals involved. It follows the deductive method under a qualitative approach of an interpretive type, structured under a topical narrative design. The curriculum for the physical education career must respond to the very nature of the specialty while proposing significant learning situations for the fundamentals of sports since the latter goes beyond physical activities. Also, they instill and strengthen values such as respect, responsibility, commitment, and dedication while helping in socialization